An Empirical Study of Relationship between Working Capital Management and Leverage in Selected Petroleum Companies in India - Yousif Hameed Nayyef (Journal La Bisecoman, 2022)
The main purpose of this article is to find out the relationship between working capital management and leverage of selected petroleum companies in India. The management of working capital and leverage in the business organization has been considered as very crucial part in financial management. Working capital considered as surplus of current assets over current liabilities and leverage considered as firm’s ability of employing long term fund having a fixed cost for the purpose of increasing the return of the real owner of the organization. The evaluation of relationship between the two variables and it is identified with the help of parametric test like correlation analysis and one-way ANOVA. The major findings of the study indicated that there is mixed relationship between working capital and leverage position because with the help of correlation analysis Reliance Petroleum, ONGC (Oil and Nature Gas Corporation Limited), IOCL (Indian Oil Corporation Limited), BPCL (Bharat Petroleum Corporation Limited) indicated positive relationship between two variables. GAIL (Gas Authority of India Limited) indicated negative relationship between working capital and leverage during the study period.